Application of the method of the ten commandments and development of capabilities in the area of mathematics - Cámara-Acero, Andrés A. (2019)
With the purpose of deepening the analysis and interpretation of the results the design was in use cuasi experimentally and by means of the sampling probabilístic there was chosen a workgroup shaped by 105 pupils of the Faculty of sciences of the education, matriculated persons in the academic year 2011 in the area of mathematics. To the groups experimental (55) and control (50) applied a pre to him it tries and post tries 15 questions, both expressed in the system vigesimal. To estimate the statisticians one used the descriptive statistics and for the contrastación of the hypothesis the distribution test of averages was applied. Of The analysis there is inferred that the final average of the experimental group is of 14, which demonstrates that the achievement of the learnings is satisfactory; and with regard to the group control the final average is 12, which demonstrates light difficulties for the development of the foreseen learning and needs major time of accompaniment and intervention of the teacher of agreement with his pace and style of learning. The level of development of capacities of the pupils of the experimental group with regard to the area of mathematics on having finished the study, improves significantly with the application of the method ten orders, in comparison with the pupils of the group control that they did not receive the application of the same one.